Method for preparing municipal road lime-fly ash base stabilizing material by using construction waste recycled aggregate in large mixing amount
By screening the recycled aggregate of construction waste and determining the particle grading ratio and the mixing ratio of lime and fly ash, a stable material of lime fly ash is prepared, which solves the problems of low dosage and unstable performance, and realizes construction waste 100% replaces natural aggregates, improving utilization and material performance.
Patent Information
- Application Number
- CN202411243428.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-05
- Publication Date
- 2024-12-13
AI Technical Summary
In the prior art, the recycled aggregate of construction waste is used to prepare municipal road base materials with low dosage and unstable performance, resulting in poor construction waste treatment effect and poor economic and environmental protection effect.
By screening the recycled aggregate of construction waste, the particle grading ratio is determined, and the combination ratio of lime, fly ash and synthetic recycled aggregate is determined based on the results of the impact test and compressive strength, lime fly ash is prepared. The base layer stabilizes the material to achieve 100% replacement of natural aggregate for recycled aggregate for construction waste.
It has achieved 100% replacement of natural aggregate for construction waste, improved the utilization rate of construction waste, reduced the cost of garbage storage and engineering materials, improved the ecological environment, excellent material performance, and complied with relevant technical specifications.
Smart Images

Figure CN119118611A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of road engineering, and in particular to a method for preparing a lime fly ash base stabilizing material for a municipal road by using a large amount of recycled aggregate from construction waste. Background Art
[0002] With the acceleration of urbanization, the output of construction waste has increased dramatically, bringing great pressure to the environment. Traditional methods of construction waste disposal, such as landfill or transportation, not only occupy a large amount of land resources, but also may cause environmental pollution and waste of resources. Therefore, the resource utilization of construction waste has become an important topic at present. By utilizing recycled construction waste, the exploitation of natural resources can be significantly reduced, environmental pollution can be reduced, and sustainable development can be achieved. At present, the use of recycled aggregates from construction waste to prepare municipal road base materials has gradually been applied in actual projects as a way to treat and utilize recycled aggregates from construction waste.
[0003] However, in the existing methods for preparing municipal road base materials, due to the characteristics of recycled aggregates from construction waste such as a wide variety of components and complex properties, the amount of recycled aggregates from construction waste used to prepare municipal road base materials is low, and the performance of the prepared base materials is unstable, the amount of construction waste absorbed is small, the effect on the absorption of construction waste is weak, and the economic and environmental effects are poor. Summary of the invention
[0004] The present invention provides a method for preparing a municipal road lime fly ash base stabilizing material by using a large amount of recycled aggregate from construction waste, so as to solve the above problems.
[0005] In order to achieve the above object, the technical solution of the present invention is:
[0006] A method for preparing a municipal road lime fly ash base stabilization material by using a large amount of construction waste recycled aggregate, comprising the following steps:
[0007] S1: Screen the recycled aggregate from construction waste to determine the particle grading ratio:
[0008] The recycled aggregates of construction waste are crushed and divided into recycled coarse aggregate and recycled fine aggregate according to the particle size specifications. The gradation ratio of the recycled coarse aggregate and the recycled fine aggregate is determined according to the crushing index, water absorption rate and gradation curve of the recycled coarse aggregate and the recycled fine aggregate, ensuring that the crushing index, water absorption rate and gradation curve of the recycled coarse aggregate and the recycled fine aggregate meet the corresponding design requirements. The recycled coarse aggregate and the recycled fine aggregate are mixed to form a synthetic recycled graded aggregate;
[0009] S2: Determine the mix ratio of lime, fly ash and synthetic recycled graded aggregate:
[0010] Determine the mix ratio of lime, fly ash and synthetic recycled graded aggregate according to the optimum moisture content, maximum dry density and 7d unconfined compressive strength of the mixed materials to ensure that the optimum moisture content, maximum dry density and 7d unconfined compressive strength meet the corresponding design requirements;
[0011] S3: Preparation of lime fly ash base stabilization materials for municipal roads:
[0012] The synthetic recycled graded aggregate is prepared by mixing the recycled coarse aggregate and the recycled fine aggregate in the proportion determined in S1, and the lime, fly ash and the synthetic recycled graded aggregate are mixed in the amounts determined in S2 to obtain the municipal road lime fly ash base stabilization material; lime, as an inorganic cementitious material, can react with the recycled aggregate particles to form a high-strength combination. Fly ash has volcanic ash activity and can react with lime and recycled aggregate to generate a cementitious substance, thereby improving the strength and durability of the base.
[0013] Furthermore, in S2, the mass ratio of the lime, fly ash and synthetic recycled graded aggregate is 7:13:80.
[0014] Furthermore, in S1, the recycled coarse aggregate includes two particle sizes of 5 to 10 mm and 10 to 25 mm; the recycled fine aggregate includes one particle size of 0 to 5 mm;
[0015] The mixing ratio of the 0-5 mm recycled fine aggregate, the 5-10 mm recycled coarse aggregate and the 10-25 mm recycled coarse aggregate is 24:26:50.
[0016] Furthermore, in S2, the number of compaction tests was no less than 3 times, the average optimum moisture content was 10.2%, and the average maximum dry density was 1.974 g / cm 3 .
[0017] Furthermore, in S1, the crushing index is: the crushing rate of recycled coarse aggregate is less than 22%, and the crushing rate of recycled fine aggregate is less than 30%.
[0018] Furthermore, in S1, the water absorption index is less than 9.5%.
[0019] Furthermore, in S2, the 7d unconfined compressive strength is not less than 1.90 MPa.
[0020] Furthermore, in S1, the gradation curve specification requirements for recycled coarse aggregate and recycled fine aggregate are:
[0021] The upper limit of gradation of 19.0mm recycled coarse aggregate is 86.0% and the lower limit is 68.0%;
[0022] The upper limit of gradation of 9.5mm recycled coarse aggregate is 58.0% and the lower limit is 38.0%;
[0023] The upper limit of gradation of 4.75mm recycled fine aggregate is 32.0% and the lower limit is 22.0%;
[0024] The upper limit of gradation of 2.36mm recycled fine aggregate is 28.0% and the lower limit is 16.0%;
[0025] The upper limit of gradation of 0.60mm recycled fine aggregate is 15.0% and the lower limit is 8.0%;
[0026] The upper limit of grading of 0.075mm recycled fine aggregate is 3.0% and the lower limit is 1.0%.
[0027] Furthermore, the fly ash is Class II fly ash.
[0028] Furthermore, the lime is calcareous grade III slaked lime.
[0029] The beneficial effects of the present invention are:
[0030] The invention discloses a method for preparing a lime fly ash base stabilizing material for a municipal road by using a large amount of recycled aggregate from construction waste. The method comprises the following steps: firstly, the representative recycled aggregate from construction waste is screened and the particle grading ratio of the recycled aggregate is determined in combination with relevant index parameter requirements; then, the mix ratio of lime, fly ash and synthetic recycled graded aggregate is determined according to the compaction test result and the compressive strength; finally, the lime fly ash base stabilizing material is prepared by mixing the particle grading ratio of the recycled aggregate and the mix ratio between the materials; the method breaks the technical bottleneck of low recycled aggregate dosage, realizes that 100% of recycled aggregate from construction waste replaces natural aggregate to prepare the base stabilizing material for a municipal road, can turn construction waste into treasure, greatly improve the utilization rate of construction waste, reduce garbage storage, release land resources, reduce the cost of engineering materials, alleviate the mining pressure of natural materials, improve ecological environment problems, have a positive impact and practical value on promoting the rapid development of the construction waste resource utilization industry and improving the resource utilization rate of construction waste in my country, and is also a substantial strategy for building a circular economy and an environmentally friendly and resource-saving society; at the same time, the material meets the requirements of relevant technical specifications, has excellent performance, and has technical performance for engineering use. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for use in the embodiments or the description of the prior art. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0032] Figure 1 It is a flow chart of a method for preparing a lime fly ash base stabilization material for a municipal road by using a large amount of recycled aggregate from construction waste disclosed in an embodiment of the present invention;
[0033] Figure 2 The results of the screening test of recycled aggregates of different specifications are shown in the figure;
[0034] Figure 3 Synthesize gradation curves for recycled aggregates of different specifications;
[0035] Figure 4 This is a graph showing the compaction test results of a municipal road lime fly ash base stabilized material prepared by a method for preparing a municipal road lime fly ash base stabilized material using a large amount of recycled aggregate from construction waste disclosed in an embodiment of the present invention;
[0036] Figure 5 This is a graph showing the unconfined compressive strength test results of a municipal road lime fly ash base stabilized material prepared by a method for preparing a municipal road lime fly ash base stabilized material using a large amount of recycled aggregate from construction waste disclosed in an embodiment of the present invention. DETAILED DESCRIPTION
[0037] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0038] Example:
[0039] like Figure 1 The method for preparing a municipal road base stabilizing material using a large amount of recycled aggregate from construction waste provided in this embodiment includes the following steps:
[0040] S1: Screen the recycled aggregate from construction waste to determine the particle grading ratio:
[0041] Recycled aggregates from construction waste include waste concrete, bricks and a small amount of tiles. The recycled aggregates from construction waste are crushed and divided into 0-5mm recycled fine aggregate, 5-10mm recycled coarse aggregate and 10-25mm recycled coarse aggregate. The three sizes of recycled aggregates are screened and tested. The test results are as follows: Figure 2 As shown by Figure 2It can be seen that the gradation composition of recycled aggregate is poor, and the particle size is relatively concentrated, especially in the 5-10mm aggregate, about 90% of the aggregate is concentrated around 5mm. In order to prevent the particle size distribution from restricting the bulk density and compressive performance and affecting the structural characteristics of the road base, it is necessary to blend the three types of aggregate; the mixing ratio of recycled coarse aggregate and recycled fine aggregate is determined according to the crushing index and water absorption rate after the recycled coarse aggregate and recycled fine aggregate are mixed, ensuring that the crushing index meets the recycled coarse aggregate crushing rate less than 22%, the recycled fine aggregate crushing rate less than 30%, and the water absorption rate less than 9.5%, and the gradation curve between the three must meet the upper and lower limits of the gradation required by the specification. Specifically, the gradation upper limit of 19.0mm recycled coarse aggregate is 86.0%, and the lower limit is 68. .0%; the upper limit of the gradation of 9.5mm recycled coarse aggregate is 58.0%, and the lower limit is 38.0%; the upper limit of the gradation of 4.75mm recycled fine aggregate is 32.0%, and the lower limit is 22.0%; the upper limit of the gradation of 2.36mm recycled fine aggregate is 28.0%, and the lower limit is 16.0%; the upper limit of the gradation of 0.60mm recycled fine aggregate is 15.0%, and the lower limit is 8.0%; the upper limit of the gradation of 0.075mm recycled fine aggregate is 3.0%, and the lower limit is 1.0%, so that the proportion of 0-5mm recycled fine aggregate, 5-10mm recycled coarse aggregate and 10-25mm recycled coarse aggregate is determined to be 24:26:50, and the three are mixed to form a synthetic recycled graded aggregate. The gradation ratio curve is as follows Figure 3 As shown in the figure, the gradation curve is close to the middle value of the design gradation and meets the upper and lower limits of the gradation required by the specification, which meets the design requirements. At the same time, when designing the gradation ratio of 0-5mm recycled fine aggregate, 5-10mm recycled coarse aggregate and 10-25mm recycled coarse aggregate, consideration should be given to avoiding contact damage caused by the inter-particle inter-extrusion effect to ensure the strength and stability of the material.
[0042] S2: Determine the amount of lime, fly ash and synthetic recycled graded aggregate:
[0043] The mixing ratio of the three is determined based on the optimum moisture content and maximum dry density measured by three compaction tests on the mixed materials of lime, fly ash and synthetic recycled graded aggregate, as well as the 7d unconfined compressive strength of the infinite lateral compressive strength test, ensuring that the average optimum moisture content is 10.2% and the average maximum dry density is 1.974g / cm 3, 7d unconfined compressive strength is not less than 1.90MPa, fly ash is grade II fly ash, and lime is calcium grade III slaked lime; according to the above design requirements, the mass ratio of lime, fly ash and synthetic recycled graded aggregate is determined to be 7:13:80. In this embodiment, the mass of lime is 455.0g, the mass of fly ash is 845.0g, and the mass of synthetic recycled graded aggregate is 5200g. In the synthetic recycled graded aggregate, the mass of 0-5mm recycled fine aggregate is 1248g, the mass of 5-10mm recycled coarse aggregate is 1352g, and the mass of 10-25mm recycled coarse aggregate is 2600g;
[0044] S3: Preparation of lime fly ash base stabilization materials for municipal roads:
[0045] The recycled coarse aggregate and the recycled fine aggregate are mixed in the proportion determined in S1 to prepare synthetic recycled graded aggregate, and the materials are mixed in the amounts of lime, fly ash and synthetic recycled graded aggregate determined in S2 to prepare the lime fly ash base stabilization material for municipal roads.
[0046] Performance Test:
[0047] (1) Compaction test:
[0048] Lime, fly ash and synthetic recycled graded aggregate were used to prepare the municipal road lime fly ash base stabilization material, and compaction tests with water contents of 8.0%, 9.0%, 10.0%, 10.5% and 11.0% were performed respectively (i.e., 5 compaction tests were performed). Two groups were set for each test, and the average value of the results of the two groups of tests was taken. Table 1 shows the test results. Figure 4 is the compaction curve, from Table 1 and Figure 4 It can be seen that the optimal moisture content of the lime fly ash base stabilization material for municipal roads is 10.2%, and the maximum dry density is 1.974 g / cm 3 Therefore, the lime fly ash base stabilization material for municipal roads is prepared according to the mass ratio of lime, fly ash and synthetic recycled graded aggregate of 7:13:80 to meet the corresponding design requirements;
[0049] Table 1 Compaction test results
[0050]
[0051] (2) Unconfined compressive strength test:
[0052] According to the compaction test results, in order to verify whether the mechanical properties of the lime fly ash base stabilized material prepared by the mix ratio of the above lime, fly ash and synthetic recycled graded aggregate meet the requirements of relevant specifications, referring to the "Test Code for Inorganic Binder Stabilized Materials for Highway Engineering" (JTG 3441-2024), a Φ150mm×150mm specimen was used, and the pressure testing machine was pressurized at a loading rate of 1mm / min, and the pressure was maintained for 2min for compaction. When immersed in water, it was immersed in 20±2℃ water. Unconfined compressive strength tests were carried out at ages of 1d, 3d, 14d, and 28d. The test results are as follows: Figure 5 As shown by Figure 5 It can be seen that the unconfined compressive strength of the specimen at the age of 7d is 1.90MPa, which meets the design requirements and has far exceeded the technical requirement of 1.1MPa for the 7d unconfined compressive strength of extra-heavy and extremely-heavy traffic on expressways in the "Technical Specifications for Construction of Highway Pavement Base" (JTG / T F20-2015); among them, the strength of the specimen at the age of 3d is 1.07MPa, which is close to meeting the technical requirement of 7d unconfined compressive strength of extra-heavy and extremely-heavy traffic on expressways in the specifications.
[0053] (3) Antifreeze performance test
[0054] In order to verify that the frost resistance of the lime fly ash stabilized recycled aggregate prepared by the mix ratio of the above lime, fly ash and synthetic recycled graded aggregate meets the requirements of the "Test Code for Stabilized Materials with Inorganic Binders for Highway Engineering" (JTG 3441-2024), an frost resistance test was carried out with reference to the "Test Code for Stabilized Materials with Inorganic Binders for Highway Engineering" (JTG 3441-2024). The test results are shown in Table 2. It can be seen from the results in Table 2 that the mass loss rate of the specimen after freeze-thaw is less than 5%, and the residual compressive strength ratio of the specimen after freeze-thaw is greater than 70%. Therefore, the lime fly ash stabilized recycled aggregate prepared in this ratio exhibits good frost resistance.
[0055] Table 2 Antifreeze performance test results
[0056]
[0057] In summary, the lime fly ash base material for municipal roads prepared by the particle grading ratio of recycled aggregate from construction waste and the mix ratio of lime, fly ash and synthetic recycled graded aggregate determined by a method of preparing lime fly ash base stabilization material for municipal roads with large amounts of recycled aggregate from construction waste has an unconfined compressive strength of 1.90 MPa, the mass loss rate of the specimen after freeze-thaw is less than 5%, and the residual compressive strength ratio of the specimen after freeze-thaw is greater than 70%, showing good performance, greatly improving the utilization rate of construction waste, reducing the cost of engineering materials, and ensuring the performance of the material, which plays a positive role in promoting the development of green building materials, promoting circular economy, and improving the quality and durability of road projects.
[0058] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing a municipal road lime fly ash base stabilization material using a large amount of construction waste recycled aggregate, characterized in that: The following steps are involved: S1: Screen the recycled aggregate from construction waste to determine the particle grading ratio: The recycled aggregates of construction waste are crushed and divided into recycled coarse aggregate and recycled fine aggregate according to the particle size specifications. The gradation ratio of the recycled coarse aggregate and the recycled fine aggregate is determined according to the crushing index, water absorption rate and gradation curve of the recycled coarse aggregate and the recycled fine aggregate, ensuring that the crushing index, water absorption rate and gradation curve of the recycled coarse aggregate and the recycled fine aggregate meet the corresponding design requirements. The recycled coarse aggregate and the recycled fine aggregate are mixed to form a synthetic recycled graded aggregate; S2: Determine the mix ratio of lime, fly ash and synthetic recycled graded aggregate: Determine the mix ratio of lime, fly ash and synthetic recycled graded aggregate according to the optimum moisture content, maximum dry density and 7d unconfined compressive strength of the mixed materials to ensure that the optimum moisture content, maximum dry density and 7d unconfined compressive strength meet the corresponding design requirements; S3: Preparation of lime fly ash base stabilization materials for municipal roads: The recycled coarse aggregate and the recycled fine aggregate are mixed in the proportion determined in S1 to prepare synthetic recycled graded aggregate, and the materials are mixed in the amounts of lime, fly ash and synthetic recycled graded aggregate determined in S2 to prepare the lime fly ash base stabilization material for municipal roads.
2. The method for preparing a municipal road lime fly ash base stabilization material by using a large amount of recycled aggregate from construction waste according to claim 1, characterized in that: In S2, the mass ratio of the lime, fly ash and synthetic recycled graded aggregate is 7:13:
80.
3. The method for preparing a municipal road lime fly ash base stabilization material by using a large amount of construction waste recycled aggregate according to claim 1, characterized in that: In S1, the recycled coarse aggregate includes two particle sizes of 5-10 mm and 10-25 mm; the recycled fine aggregate includes one particle size of 0-5 mm; The mixing ratio of the 0-5 mm recycled fine aggregate, the 5-10 mm recycled coarse aggregate and the 10-25 mm recycled coarse aggregate is 24:26:
50.
4. The method for preparing a municipal road lime fly ash base stabilization material by using a large amount of construction waste recycled aggregate according to claim 1, characterized in that: In S2, the number of compaction tests is not less than 3 times, the average optimum moisture content is 10.2%, and the average maximum dry density is 1.974g / cm 3 .
5. The method for preparing municipal road lime fly ash base stabilization material by using large amount of construction waste recycled aggregate according to claim 1, characterized in that: In S1, the crushing index is: the crushing rate of recycled coarse aggregate is less than 22%, and the crushing rate of recycled fine aggregate is less than 30%.
6. The method for preparing municipal road lime fly ash base stabilization material by using large amounts of recycled aggregate from construction waste according to claim 1, characterized in that: In S1, the water absorption index is less than 9.5%.
7. The method for preparing a municipal road lime fly ash base stabilization material by using a large amount of recycled aggregate from construction waste according to claim 1, characterized in that: In S2, the 7d unconfined compressive strength is not less than 1.90MPa.
8. The method for preparing municipal road lime fly ash base stabilization material by using large amounts of recycled aggregate from construction waste according to claim 3, characterized in that: In S1, the gradation curve specification requirements for recycled coarse aggregate and recycled fine aggregate are: The upper limit of gradation of 19.0mm recycled coarse aggregate is 86.0% and the lower limit is 68.0%; The upper limit of gradation of 9.5mm recycled coarse aggregate is 58.0% and the lower limit is 38.0%; The upper limit of gradation of 4.75mm recycled fine aggregate is 32.0% and the lower limit is 22.0%; The upper limit of gradation of 2.36mm recycled fine aggregate is 28.0% and the lower limit is 16.0%; The upper limit of gradation of 0.60mm recycled fine aggregate is 15.0% and the lower limit is 8.0%; The upper limit of grading of 0.075mm recycled fine aggregate is 3.0% and the lower limit is 1.0%.
9. The method for preparing municipal road lime fly ash base stabilization material by using large amounts of recycled aggregate from construction waste according to claim 1, characterized in that: The fly ash is Class II fly ash.
10. The method for preparing municipal road lime fly ash base stabilization material by using large amounts of recycled aggregate from construction waste according to claim 1, characterized in that: The lime is calcareous grade III slaked lime.
Citation Information
Patent Citations
Product relevant with lime-coal ash-coagulator stabilized recycled aggregate
CN108238772A
Lime-ash stabilized building garbage regenerated mixture and preparation method thereof
CN109020430A
Building solid waste regenerated composite roadbed filler and preparation method thereof
CN111393065A
Mixed material of regenerated building residue and its prepn process
CN1931775A
